Freedom Of Religion And Belief Under Supreme Court Verdict Study Case On Supreme Court Decision Number 17/P/HUM/2021 - Zainal Amin Ayub; Ari Wirya Dinata; Nur Sulistyo Budi Ambarini; Pipi Susanti; Arie Elcaputera (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
Freedom of religion or belief (FoRB) is one of the human rights stated in the 1945 Constitution. Article 29 paragraphs (1) and (2) of the 1945 Constitution. The recognition of religion guarantees the independence of each of its inhabitants to embrace their respective religions and to worship according to their religion or beliefs. The state guarantee on FoRB consists of assurance for the internal and external forums. Freedom to embrace religion or belief is an internal forum for everyone, an absolute right as regulated in ICCPR that Indonesia has also ratified. In fact, this provision is also regulated in Article 28 I paragraph (1) of the 1945 Constitution. The fulfillment of the right to FoRB is frequently discriminated against in Indonesia. The issue of forcing to wear school uniforms with hijab for non-Muslim female students is still common in many public schools in Indonesia. The State has issued a joint decree (SKB) of 3 ministers to normalize the discriminatory status quo. However, the attempt to return it to its normal position was thwarted by the LKMM, which carried out the SKB test. Unfortunately, the Supreme Court (SC) canceled the SKB because schools have the right to carry out religious education and instilled values. The judges ratio decidendi made by the SC Justices were very dry from the perspective of freedom of religion or belief in canceling the 3 Ministerial Decrees. The judge saw the issue of forcing to wear hijab on non-Muslim students from the perspective of the majority religious thought without noticing that Indonesian society is very diverse. Therefore, the protection of the right to FoRB should also safeguard the religious minorities rights. This paper will examine decision made by judiciary power in term protecting the FoRB right. This verdict will be reviewing toward to justice consideration (ratio decedendi) and legal archicteture in filling the norm FoRB. Moreover, it will also appraise to judicial behavior based on breakfasting theory.